Question
upstudy study bank question image url

\( \begin{array}{l}7 x-3 y=4 \\ 2 x-4 y=1\end{array} \) Which of the following system of equations is not equal to the system of equations shown above? \( \begin{array}{l}14 x-6 y=4 \text { and }-14 x+28 y=1 \\ 28 x-12 y=16 \text { and }-6 x+12 y=-3 \\ -28 x+12 y=-16 \text { and } 28 x-56 y=14\end{array} \)

Ask by Mathis Wright. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The system \(14x - 6y = 4\) and \(-14x + 28y = 1\) is not equivalent to the original system.

Solution

To determine which of the given systems of equations is not equivalent to the original system, we can analyze each option by checking if they can be derived from the original equations through multiplication or addition. The original system of equations is: 1. \( 7x - 3y = 4 \) 2. \( 2x - 4y = 1 \) Let's analyze each option: ### Option 1: 1. \( 14x - 6y = 4 \) 2. \( -14x + 28y = 1 \) - The first equation can be obtained by multiplying the first equation of the original system by 2: \[ 2(7x - 3y) = 2(4) \implies 14x - 6y = 8 \quad \text{(not equal)} \] - The second equation can be obtained by multiplying the second equation of the original system by -7: \[ -7(2x - 4y) = -7(1) \implies -14x + 28y = -7 \quad \text{(not equal)} \] Thus, this system is not equivalent to the original system. ### Option 2: 1. \( 28x - 12y = 16 \) 2. \( -6x + 12y = -3 \) - The first equation can be obtained by multiplying the first equation of the original system by 4: \[ 4(7x - 3y) = 4(4) \implies 28x - 12y = 16 \quad \text{(equal)} \] - The second equation can be obtained by multiplying the second equation of the original system by -3: \[ -3(2x - 4y) = -3(1) \implies -6x + 12y = -3 \quad \text{(equal)} \] Thus, this system is equivalent to the original system. ### Option 3: 1. \( -28x + 12y = -16 \) 2. \( 28x - 56y = 14 \) - The first equation can be obtained by multiplying the first equation of the original system by -4: \[ -4(7x - 3y) = -4(4) \implies -28x + 12y = -16 \quad \text{(equal)} \] - The second equation can be obtained by multiplying the second equation of the original system by 14: \[ 14(2x - 4y) = 14(1) \implies 28x - 56y = 14 \quad \text{(equal)} \] Thus, this system is equivalent to the original system. ### Conclusion: The system of equations that is not equal to the original system is: \[ \begin{array}{l} 14x - 6y = 4 \\ -14x + 28y = 1 \end{array} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To determine which system of equations is not equivalent to the given system \( \begin{array}{l} 7x - 3y = 4 \\ 2x - 4y = 1 \end{array} \), we need to look for a transformation that might introduce inconsistencies. The first system \( 14x - 6y = 4 \) and \( -14x + 28y = 1 \) can be modified by multiplying the first equation by 2; however, the second equation does not arise from any simple manipulation of the first system, indicating a disparity. On the other hand, the second system \( 28x - 12y = 16 \) and \( -6x + 12y = -3 \) can be deduced from consistent scalar multipliers. Similarly, the last system \( -28x + 12y = -16 \) and \( 28x - 56y = 14 \) also aligns correctly based on manipulation rules. Thus, the first system is the one that does not maintain equivalency with the original given equations.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy